National Survey on Training in Pediatric Cardiology by the "Junges Forum" of the DGPK - Horst, Jan Pit; Michel, Miriam; Kubicki, Rouven; Lang, Nora; Zschirnt, Martin; Moosmann, Julia (Thoracic and Cardiovascular Surgeon, 2020)
BACKGROUND: This is the first national survey of residents and fellows in pediatric cardiology in Germany evaluating training, research activity, and the general working environment. METHODS: An online questionnaire including 62 questions (SurveyMonkey) was developed by the "Junges Forum" of the German Society of Pediatric Cardiology. Fellows and residents during training and up to 3 years after completing their pediatric cardiology fellowship were invited to participate. RESULTS: A total of 102 pediatric cardiology fellows and residents completed the questionnaire. Many participants complained about their training as being unstructured (47%) and non-transparent (37%). The numbers of technical and catheter interventions required by the national medical board in Germany cannot be achieved, especially regarding invasive procedures. Sixty per cent work more than contractually agreed, usually in Germany it is 40 hours daytime work plus on calls, while 90% of all participants prefer less than 50 weekly working hours; 50% of the participants are engaged in research that is usually done during their spare time. More than 90% are satisfied with their professional relationships with colleagues and coworkers. Seventy-eight per cent describe their career perspectives as promising, and 84% would start a fellowship in pediatric cardiology again. CONCLUSION: The majority of pediatric cardiology fellows and residents are satisfied with their working environment and with their choice of a career in pediatric cardiology. Besides the heavy work load, we identified the urgent desire for better structured transparent clinical training concept including the teaching of manual skills, i.e., invasive procedures and catheterization.
CRIS-Team Scopus Importer:2020-03-13